Effects of TiB2 content on the processability and mechanical performance of Hastelloy-X based composites fabricated by selective laser melting. (November 2022) - Yang, Shengzhao; Han, Quanquan; Yin, Yingyue; Zhang, Zhenhua; Wang, Liqiao; Zhu, Zuoxin; Liu, Hanlian; Ma, Teng; Gao, Zhengjiang
Highlights: The TiB2 addition promoted grain refinement in SLM-fabricated HX-TiB2 composites. Effects of TiB2 content on processability of HX- TiB2 composites investigated. Strong interfacial bonding formed in HX-1% TiB2 /HX-3% TiB2 gradient composites. Abstract: Nickel-based Hastelloy X (HX) superalloy is susceptible to cracking when processed by selective laser melting (SLM) process. Previous studies have reported that the microcracks may be eliminated by adding 2 wt% TiB2 ceramic particles, while the modified HX materials are generally classified as HX-based composites. An investigation of the effects of different TiB2 contents (i.e. 1 wt% and 3 wt%) on SLM of HX-TiB2 composites would thus be interesting in terms of the processability, microstructure and mechanical performance. The results indicate that compared to pure HX, microcracks were not detected in the SLM-fabricated neither the HX- 1 wt% TiB2 (HX-1) nor the HX-3 wt% TiB2 (HX-3) composites due to the significant grain-refinement behaviour. The microcracks elimination together with the added TiB2 particles also contributed to a remarkable improvement in the composites' tensile performance. The determined ultimate tensile strength of HX-1 and HX-3 were 77% and 106% higher than that of pure HX at 850 ℃, respectively. This research also explored the processability and microstructure of HX-TiB2 graded composites by combining the HX-1 and HX-3 via the SLM process, which offers a promising pathway to manufacture advanced components with graded structures and materials via the SLM process.